2009
DOI: 10.1186/1471-2334-9-153
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping of Streptococcus agalactiae(group B streptococci) isolated from vaginal and rectal swabs of women at 35-37 weeks of pregnancy

Abstract: BackgroundGroup B streptococci (GBS), or Streptococcus agalactiae, are the leading bacterial cause of meningitis and bacterial sepsis in newborns. Here we compared different culture media for GBS detection and we compared the occurrence of different genotypes and serotypes of GBS isolates from the vagina and rectum.MethodsStreptococcus agalactiae was cultured separately from both rectum and vagina, for a total of 150 pregnant women, i) directly onto Columbia CNA agar, or indirectly onto ii) Granada agar resp. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 48 publications
(57 reference statements)
3
37
2
Order By: Relevance
“…DNA was extracted from cultured isolates by alkaline lysis as previously described [15]. Briefly, one bacterial colony was suspended in 20 μl of lysis buffer (0.25% sodium dodecyl sulfate, 0.05 N NaOH) and heated at 95 °C for 15 min.…”
Section: Methodsmentioning
confidence: 99%
“…DNA was extracted from cultured isolates by alkaline lysis as previously described [15]. Briefly, one bacterial colony was suspended in 20 μl of lysis buffer (0.25% sodium dodecyl sulfate, 0.05 N NaOH) and heated at 95 °C for 15 min.…”
Section: Methodsmentioning
confidence: 99%
“…Rectovaginal swabs have been reported to provide high bacterial yields [10,25,[30][31][32] and have therefore been recommended for GBS screening [10]. However, Nomura et al [33] found no significant difference in detection rates between vaginal and rectal samples and Gupta and Briski [34] reported a similar detection rate of 23.8% of GBS when using rectovaginal and vaginal sampling.…”
Section: Introductionmentioning
confidence: 81%
“…Meyn et al [28] showed that rectal colonization with GBS was the most significant predictor of vaginal colonization, suggesting that the vagina becomes colonized with GBS as a result of transfer of the organism from the rectum to the vagina. Our previous culture-based genotyping study showed a high correspondence of vaginal and rectal colonization with GBS, also at the strain level [25], because a total of 19 women was colonized by GBS in both rectum and vagina and moreover, 18 of these women had at least one vaginal and one rectal isolate with the same genotype.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We can say that species belonging to genera such as Mycobacterium, Staphylococcus and Streptococcus have caused altogether > 700 million cases of infections annually, with > 2 million deaths [81][82][83][84] due to both community-acquired and nosocomial infections. In the particular case of nosocomial infections, other genera like Enteroroccus, Pseudomonas and Escherichia (and many others) have inflicted a serious impact in health-care facilities around the world, exhibiting high mortalities rates even in developed countries [85].…”
Section: Virtual Simultaneous Prediction Of Antibacterial Activities mentioning
confidence: 99%